Sexual Frequency Decline From Midlife to Later Life - Karraker, Amelia (Oxford University Press, 2011)
OBJECTIVE. To examine sexual frequency decline among American men and women between the ages of 44 and 72 born from 1933 to 1948. METHOD. Using data from the National Health and Social Life Survey (NHSLS) and the National Social Life, Health, and Aging Project (NSHAP), the decline in sexual frequency is decomposed into declines due to changes in marital status, physical health, and happiness. We examine the contribution of both changes in the composition of the population with respect to these factors as well as changes in the association between these factors and sexual frequency by age. RESULTS. For women, change in the proportion widowed is a significant factor in sexual frequency decline, as is change in the association between happiness and sexual frequency. Among men, both poorer physical health at older ages and a decrease in its association with frequency are significant factors in the decline. A change in the association between happiness and frequency is also a significant factor for men. Reverse causality may explain the happiness–frequency findings for both men and women. DISCUSSION. Results provide evidence for gendered experiences in the sexual life course.